PENGARUH PENDIDIKAN KARAKTER TERHADAP KECERDASAN EMOSIONAL SISWA SEKOLAH DASAR - Jusniari Siregar; Riki Hamdan Saputra; Rani Astria Silvera Harahap; Era Mutiah (Titik Fokus Karya, 2025)
Based on the results of this study aims to determine whether character education affects the emotional intelligence of students of SD Negeri 1007 Tanjung Baringin. This research uses quantitative methods involving all students of SD Negeri 1007 Tanjung Baringin. The sample amounted to 51 students. Data collection techniques include questionnaires and documents, Data analysis was carried out using descriptive statistics and prerequisite tests. This study shows that character education has a significant influence on emotional intelligence. For the ANOVA test, the F value is 74.085 and the significance level is 0.000 <. 0,05. Furthermore, in the t test, the coefficient (X) of the personality development variable is 0.384, the constant is 49.683, and the sig column value shows tcount <. Table (0.000 < 0.05). This shows that character education has a significant influence on students' emotional intelligence (Ha is accepted and H0 is rejected). For the R-squared test, the R-squared value is 0.458 (45.8%). This means that character education contributes 45.8% to students' emotional intelligence and 54.2% is influenced by other variables not included in this study